Long-Lasting Verbatim Memory for the Words of Books After a Single Reading Without Any Learning Intention - Kuhbandner, Christof (Frontiers in Psychology, 2020)
The present study reveals an intriguing ability of our human memory: When reading a book once without any intention of learning, we store long-lasting verbatim memories of the words written in the book without being aware of it. Participants read a book chapter consisting of 32 pages (3,772 words) once without knowing that their memory would be tested later. In memory tests immediately after reading and one week after reading, they were asked to remember exactly which word was written at a specific position in the book chapter. Only memory for words was tested that were theme-unrelated and non-central. To measure memory, a two-alternative forced choice recognition test was used where a page was shown either as read before or with the replacement of one single word by a synonym. For each response, participants indicated whether the response was based on phenomenal memory experience or guessing. In the immediate test, participants claimed to have phenomenal memory experience for about a quarter the tested positions, truly remembering the word in about half of cases. In the one-week-delayed test, phenomenal memory experience was nearly entirely absent and completely uninformative. When claiming to have no phenomenal memory experience, participants still truly remembered the word for about 10% of the tested positions in both the immediate and the one-week-delayed test, without any forgetting. These findings demonstrate that we store more from read texts in memory than commonly believed.